2022
DOI: 10.3389/fpubh.2022.895538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating spatial accessibility to COVID-19 vaccine resources in diversely populated counties in the United States

Abstract: This study examines the accessibility to COVID-19 vaccination resources in two counties surrounding Newark, NJ in the New York Metropolitan Area, United States. The study area represents diverse population makeups. COVID-19 vaccines were made available by different types of vaccination sites including county mass vaccination sites, medical facilities and pharmacies, and a FEMA community vaccination center in spring 2021. We used the two-step floating catchment area method to measure accessibility and calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…At the time of writing of this article, there have been several papers recently published mapping COVID-19 vaccine accessibility, but none that have focused specifically on pediatric populations. 1820 We showed that the areas of highest accessibility within King County were located in Seattle and the immediately adjacent suburbs. In particular, the southernmost neighborhoods of Seattle and the suburbs of Renton, Newcastle, and Mercer Island had the highest accessibility scores.…”
Section: Discussionmentioning
confidence: 93%
“…At the time of writing of this article, there have been several papers recently published mapping COVID-19 vaccine accessibility, but none that have focused specifically on pediatric populations. 1820 We showed that the areas of highest accessibility within King County were located in Seattle and the immediately adjacent suburbs. In particular, the southernmost neighborhoods of Seattle and the suburbs of Renton, Newcastle, and Mercer Island had the highest accessibility scores.…”
Section: Discussionmentioning
confidence: 93%
“…The two-step floating catchment area(2SFCA) method is a widely used approach for evaluating the accessibility of facilities or services [ 18 , 19 , 23 ]. Compared to other methods (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The Huff model considers facility scale and distance factors; however, the scale of demand points is not included in the model [ 17 ]. In contrast, the 2SFCA method is advantageous as it considers multiple factors such as distance, supply and demand point facilities, etc [ 18 , 19 ]. This approach has been effectively employed in studies related to public health, such as assessing the spatial accessibility of COVID-19 patients to healthcare facilities in Florida [ 18 ], and evaluating the spatial accessibility of COVID-19 vaccine resources in the United States [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to assessing equity, Zhang also assessed the efficiency of resource allocation in PHC from an input-output perspective [16]. Some scholars have also analyzed the extent to which the distribution of health resources was spatially equitable in terms of geographic accessibility [17]. In addition, there are studies that show possible future trends in health resources through predictive modeling, the results of which may often be able to guide the work of the government to some extent [18,19].…”
Section: Introductionmentioning
confidence: 99%